Patterns of Physico-Chemical Interactions of Heavy Metal Lead (Pb) in the Jagir River Estuary System, Surabaya - Prasita, Viv Djanat; Mahmiah, Mahmiah; Widagdo, Supriyatno (Faculty of Geography, Universitas Gadjah Mada, 2025)
The Jagir River estuary system constitutes a significant ecosystem in Surabaya that sustains the livelihoods of the surrounding communities. Despite its importance, the river is subjected to substantial pollution originating from domestic and industrial waste. Therefore, this study aims to investigate the patterns of physicochemical interactions between lead (Pb) in the Jagir River estuary system. Water and sediment samples were collected at 5 strategic points, and the concentration of Pb was analyzed using Inductively Coupled Plasma optical emission spectrometry (ICP-OES). The correlation between Pb and various environmental parameters (temperature, salinity, DO, pH & TDS) was analyzed using Principal Component Analysis (PCA). The results showed that the concentrations of Pb in the water column and sediment were 0.1637 – 1.8905 ppm and 0.0735 – 0.2349 ppm, respectively, exceeding the established quality standards for water. Pb content in the waterbody exhibited an increasing trend from upstream to the sea. These results show the salinity and tidal parameters as characteristic features of the Jagir River estuary system, which influence Pb content in water and sediment. The distinct characteristics of this estuary system vary for each region or location, showing that the results can contribute to the development of environmental policies and monitoring of water quality.Received: 2024-08-15 Revised: 2024-09-12 Accepted: 2025-01-25 Published: 2025-04-28